2022
DOI: 10.7554/elife.75253
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic deep brain stimulation disrupts movement-related subthalamic nucleus activity in parkinsonian mice

Abstract: Subthalamic nucleus deep brain stimulation (STN DBS) relieves many motor symptoms of Parkinson's Disease (PD), but its underlying therapeutic mechanisms remain unclear. Since its advent, three major theories have been proposed: (1) DBS inhibits the STN and basal ganglia output; (2) DBS antidromically activates motor cortex; and (3) DBS disrupts firing dynamics within the STN. Previously, stimulation-related electrical artifacts limited mechanistic investigations using electrophysiology. We used electrical arti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 69 publications
1
16
0
Order By: Relevance
“…In the presence of constant current electrical stimulation, firing rate increases rapidly to over 200Hz at low stimulation amplitude (<0.5nA) [16,17], up to over 500Hz in some cases [18]. This was consistent with high-frequency pulsatile stimulation (>120Hz, 200µA) where firing rate of individual STN neurons was seen to increase to over 200Hz [19]. Using two oscillators to capture the mostly disconnected network, we incorporate the absence of GABAergic input from the GPe in slices by increasing the shift of the coupling function (the noughth order term, f 0 , of the Fourier series presented in Eq.6) such that the oscillators fire at around 20Hz off-stimulation (Fig 8A).…”
Section: Replication Of In Vitro Slice Experimentssupporting
confidence: 66%
“…In the presence of constant current electrical stimulation, firing rate increases rapidly to over 200Hz at low stimulation amplitude (<0.5nA) [16,17], up to over 500Hz in some cases [18]. This was consistent with high-frequency pulsatile stimulation (>120Hz, 200µA) where firing rate of individual STN neurons was seen to increase to over 200Hz [19]. Using two oscillators to capture the mostly disconnected network, we incorporate the absence of GABAergic input from the GPe in slices by increasing the shift of the coupling function (the noughth order term, f 0 , of the Fourier series presented in Eq.6) such that the oscillators fire at around 20Hz off-stimulation (Fig 8A).…”
Section: Replication Of In Vitro Slice Experimentssupporting
confidence: 66%
“…To characterize the network effect of DBS, Paulk et al mapped the cortical responses evoked by single-pulse electrical stimulation delivered via intracranial electrodes in epilepsy patients and confirmed that DBS evoked broad network responses that were stimulation location and pulse parameter dependent 26 . Finally, using cellular fluorescent calcium imaging techniques, a couple of recent studies in animal models demonstrated that DBS altered the relationship of intracellular calcium dynamics and behavior, supporting a network effect of DBS [27][28][29] .…”
mentioning
confidence: 90%
“…13 The beneficial effects of STN-DBS are not meant to be so simple and may include excitation or inhibition of various neuronal elements, such as afferent and efferent axons and soma in the STN, but at least one effect is likely to disrupt signal transmission through the STN and suppress cortically induced early and late excitation in the GPi. [33][34][35]…”
Section: Stereotactic Surgerymentioning
confidence: 99%
“…Restored cortically induced inhibition in the GPi through the direct pathway enables the release of an intended movement by disinhibiting thalamocortical activity 13 . The beneficial effects of STN‐DBS are not meant to be so simple and may include excitation or inhibition of various neuronal elements, such as afferent and efferent axons and soma in the STN, but at least one effect is likely to disrupt signal transmission through the STN and suppress cortically induced early and late excitation in the GPi 33‐35 …”
Section: Stereotactic Surgerymentioning
confidence: 99%